Ground-State and Thermodynamical Properties of Uranium Mononitride from Anharmonic First-Principles Theory - Per Söderlind (Applied Sciences, 2019)
We report on an advanced density-functional theory (DFT) approach for investigating the ground-state and thermodynamical properties of uranium mononitride (UN). The electronic structure for UN at zero temperature is obtained from DFT that utilizes the generalized gradient approximation (GGA) for the electron exchange and correlation functional and includes spin-orbit interaction and an extension with orbital polarization. Thermodynamical properties are computed within the quasi-harmonic approximation in the Debye−Grüneisen model while anharmonicity is captured in the self-consistent ab initio lattice dynamics (SCAILD) scheme. Anharmonic phonons have heretofore never been modeled from first-principles for UN but they turn out to be important. The computed free energy compares well with that of a CALPHAD (CALculation of PHAse Diagrams) assessment of available experimental data.